2021
DOI: 10.1007/s00701-021-04847-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing health-related quality of life in modified Rankin Scale grades: 15D results from 323 patients with brain arteriovenous malformation and population controls

Abstract: Background We wanted to understand how patients with different modified Rankin Scale (mRS) grades differ regarding their health-related quality of life (HRQoL) and how this affects the interpretation and dichotomization of the grade. Methods In 2016, all adult patients in our brain arteriovenous malformation (AVM) database (n = 432) were asked to fill in mailed letters including a questionnaire about self-sufficiency and lifestyle and the 15D HRQoL questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Although the use of new technologies is certainly revolutionary in this direction, the study also demonstrated certain limits that these technologies still have. In the Finnish studies of the authors Pohjola et al in 2021 [13] tested the modified Rankin Scale in patients with cerebral vascular malformations and assessed the quality of life and health of these patients and compared the results with the general population. The modified Rankin Scale showed significantly better results of the followed patients than the general population, which was measured by the original Rankin Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of new technologies is certainly revolutionary in this direction, the study also demonstrated certain limits that these technologies still have. In the Finnish studies of the authors Pohjola et al in 2021 [13] tested the modified Rankin Scale in patients with cerebral vascular malformations and assessed the quality of life and health of these patients and compared the results with the general population. The modified Rankin Scale showed significantly better results of the followed patients than the general population, which was measured by the original Rankin Scale.…”
Section: Discussionmentioning
confidence: 99%
“…The rehabilitation phase after ischemic stroke has been dedicated to the recovery of neurological function. The NIHSS [6] and mRS [23] are internationally recognized scales evaluating neurological outcomes and outcomes before and after treatment in stroke patients. In this study, after 3 months of nursing intervention of brain and heart health managers combined with "SMG" health management mode, patients' NIHSS score and mRS score improved significantly compared with routine care intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired neurological function was positively correlated with the score. Patient disability was assessed using a modified Rankin scale (mRS) [1,23], with a scale reliability and validity of 0.740, a total score of 0 to 6, and 0 indicates no neurological dysfunction, and 6 indicates death.…”
Section: Secondary Outcome Indicatorsmentioning
confidence: 99%